PENERAPAN DISIPLIN POSITIF UNTUK MENINGKATKAN KARAKTER DISIPLIN ANAK USIA DINI - Yuyun Ernawati Samad; Rusmayadi; Muhammad Akil Musi; Syamsuardi (CV. ALIM'SPUBLISHING, 2025)
This research is a qualitative research used to determine the application of positive early childhood discipline as well as supporting and inhibiting factors in its application. Data collection was carried out by observation and interview methods. The application of positive discipline in question includes the stages of application that are carried out technically and the application of positive discipline in essence, namely the application of the 7 principles of positive discipline. The results of the study show that the application of positive discipline is carried out through 3 stages, namely the socialization stage, the preparation stage and the implementation stage. The application was carried out in 10 study groups. The application is also applied by paying attention to the 7 principles of positive discipline which are the essence of positive discipline itself. The factors that support the implementation of positive discipline are the readiness of educators to continue learning, the adaptive attitude of educators, the superior personality competencies possessed by educators, adequate school facilities, the ideal number of students in each class, and the Special Curriculum owned by the Institution. The factors that hinder the implementation are that educators' understanding of the implementation of positive discipline has not been comprehensive, the role of schools in the implementation of discipline has not been carried out comprehensively, and there has been no evaluation of the results of the implementation of positive discipline.